Influence of salinity on larval development of the mangrove crab Sesarma hrockii de Man - Kannupandi, T; Vijayakumar, G; Soundarapandian, P (Indian Journal of Fisheries, 2011)
The influence of salinity on the larval development of the mangrove crab Sesarmabrockii was studied in 8 different salinities from 5 to 40 ppt with 5 ppt increment.The larval development was completed in the salinity ranged from 15 to 35 ppt with25 ppt as optimum. In the lower (5 to 10 ppt) and higher (40 ppt) salinities completemorality was recorded within 24 hours at the maximum. Further the intermoultduration of the development was shortest (18 days 10 hrs and 5 mts) in 25 ppt